A novel homobimetallic nickel complex for the asymmetric direct Mannich reaction of imines: a practical method on a multi-gram scale. Issue 96 (17th November 2017) - Zhang, Shixiong; Deng, Ping; Zhou, Jing; Liu, Mouxiong; Liang, Guojuan; Xiong, Yan; Zhou, Hui
Abstract : A practical asymmetric direct Mannich reaction catalyzed by a homobimetallic nickel complex with a low catalyst loading on a preparative scale. Abstract : A novel dinuclear Ni complex has been developed for the direct Mannich reaction of malonates with N -tosyl aryl imines with a low catalyst loading (0.1–0.05 mol%) on a preparative scale (5–50 mmol). The structure of the active species was verified via control experiments, ESI-HRMS, and DFT calculations.